JAMINAN KEPASTIAN HUKUM ATAS KELEBIHAN HASIL LELANG BARANG JAMINAN - Respati, Firmananta; Noor, Erma Zahro (Legal Standing : Jurnal Ilmu Hukum, 2024)
This study concludes that increasing customer awareness of their rights and improving the valuation process is crucial for enhancing the auction system's transparency and fairness. PT Pegadaian is recommended to strengthen its customer education efforts, collaborate with independent appraisers, and review its policies to ensure better customer rights protection. This research aims to explore the legal certainty regarding the surplus from the sale of collateral auctioned at PT Pegadaian, using a qualitative approach. The data collection methods include literature review, interviews with auction creditors, direct observation of the auction process, and document analysis. The thematic analysis approach is used to analyze the data. Data from interviews, observations, and document analysis are organized and categorized into relevant themes. The research reveals that PT Pegadaian implements an internal policy that ensures the return of the auction surplus to customers after the loan principal and administrative fees are settled. However, many customers are unaware of their rights concerning this auction surplus. Additionally, challenges arise in the auction announcement process and the appraisal of collateral, which often does not reflect market prices. The study concludes that increasing customer awareness of their rights and improving the appraisal process is essential for enhancing the transparency and fairness of the auction system.